2020
DOI: 10.1002/agj2.20142
|View full text |Cite
|
Sign up to set email alerts
|

Cutting management of alfalfa‐based mixtures in contrasting agroclimatic regions

Abstract: Cutting schedules affect forage yield, nutritive value, and persistence but few studies have recently assessed the effect of intensive cutting schedules on alfalfa (Medicago sativa L.)-based mixtures. We determined the effects of (a) cutting at early bud vs. early bloom of alfalfa, (b) a fall cut, (c) alfalfa-grass mixture vs. pure alfalfa, (d) one vs. two grasses, and (e) tall fescue (Schedonorus arundinacea [Schreb.] Dumort.) vs. timothy (Phleum pratense L.) in an experiment over four post-seeding years at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Phosphorus removal is heavily dependent on herbage accumulation, and therefore, the sole use of monoculture legumes may not be a highly effective ameliorator of phosphorus from high P soils in water-limited environments. Bélanger et al [56] reported that alfalfa grown in mixtures with at least one forage grass species had greater herbage accumulation than alfalfa grown alone, and their results were in concurrence with the results of this study. Further, the seeding rate ratio played a key role in herbage accumulation differences among the grass monocultures, and grass-legume mixtures in this study, and a similar observation was made by Adjesiwor et al [57].…”
Section: Herbage Accumulationsupporting
confidence: 91%
“…Phosphorus removal is heavily dependent on herbage accumulation, and therefore, the sole use of monoculture legumes may not be a highly effective ameliorator of phosphorus from high P soils in water-limited environments. Bélanger et al [56] reported that alfalfa grown in mixtures with at least one forage grass species had greater herbage accumulation than alfalfa grown alone, and their results were in concurrence with the results of this study. Further, the seeding rate ratio played a key role in herbage accumulation differences among the grass monocultures, and grass-legume mixtures in this study, and a similar observation was made by Adjesiwor et al [57].…”
Section: Herbage Accumulationsupporting
confidence: 91%
“…Under continental cold and humid conditions of northeastern North America, a moderate level of species diversity (about two to seven species) in intensively managed perennial forage stands generally benefits or at least maintains forage yield and reduces weeds (Bélanger et al., 2014, 2020; Deak et al., 2007, 2010; McElroy et al., 2012; Papadopoulos et al., 2012; Sanderson et al., 2005, 2012; Skinner & Dell, 2016; Tracy & Sanderson, 2004) compared to monocultures and/or to less diverse mixtures. In a multi‐criteria optimization study, Goslee et al.…”
Section: Adaptation and Resilience‐building Strategiesmentioning
confidence: 99%
“…There is some evidence, although currently limited, that this relationship between species diversity and resilience is also valid for alfalfa‐based mixtures typical of northeastern North America. In eastern Canada, year‐to‐year stability of forage yield in alfalfa‐grass mixtures (with one or two grasses) was greater than in pure alfalfa over four post‐seeding years (Bélanger et al., 2020). In Pennsylvania, lower year‐to‐year variability in forage yield with complex (five or seven species) rather than simple (two or three species) mixtures including alfalfa was shown using the IFSM model (Deak et al., 2010).…”
Section: Adaptation and Resilience‐building Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Forage yield and nutritive value of pure alfalfa and pure timothy were not assessed in this study as it is not a common practice in eastern Canada to use them in pure stands. Pure alfalfa was shown to have lower forage yield than in mixture with at least one grass species (Bélanger et al., 2020). These evaluations were carried out using IFSM for near future (2020–2049) and distant future (2050–2079) periods, and for two climatically contrasting agricultural areas in eastern Canada.…”
Section: Introductionmentioning
confidence: 99%